KONSELING SEBAYA: SEBUAH PENANGANAN MASALAH PSIKOLOGIS REMAJA PUTUS CINTA [PEER COUNSELING: A HANDLING OF POST-BREAKUP ADOLESCENT PSYCHOLOGICAL PROBLEM] - Harisma, Baiq Fifiani (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2022)
Adolescence was a period of transition from childhood to maturity which has psychological needs in the form of the need to be loved and to love which is then implemented in the form of dating relationships. But over time it will lead to the breakdown of the relationship. Therefore, this study aims to describe the using peer counseling in adolescents with psychological problems due to breakups. The method used in this study is a qualitative method with a phenomenological approach. The findings of this study are psychological problems experienced by adolescents who break up with love, namely difficulty sleeping, often crying alone at night, sometimes hitting walls, and having thoughts of suicide. Which is then exacerbated by the condition of the teenager keeping to himself and then doing peer counseling. With peer counseling, the counselee has a new understanding that the principles that must be adhered to in a relationship are seriousness and clarity of relationship and the counselee begins to be selective in choosing his life partner.